2023
DOI: 10.1186/s13690-023-01223-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness, impacts, and responses of public health emergencies towards health security: qualitative synthesis of evidence

Resham B Khatri,
Aklilu Endalamaw,
Daniel Erku
et al.

Abstract: Background Natural and human-made public health emergencies (PHEs), such as armed conflicts, floods, and disease outbreaks, influence health systems including interruption of delivery and utilization of health services, and increased health service needs. However, the intensity and types of impacts of these PHEs vary across countries due to several associated factors. This scoping review aimed to synthesise available evidence on PHEs, their preparedness, impacts, and responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Indeed, it was already emphasized that the spread of vaccine misinformation is partly correlated with hate speech and aggressive language ( 41 ). Moreover, the fact that a significant part of pandemic and vaccine misinformation was politically driven ( 6 ) warrants better communication campaigns and public health strategies which must address vaccine hesitancy and national and global action plans during health crises ( 42 ). This need maybe even more pronounced in countries such as Romania, where the level of Covid vaccination was significantly lower than the level reached in Western European countries ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was already emphasized that the spread of vaccine misinformation is partly correlated with hate speech and aggressive language ( 41 ). Moreover, the fact that a significant part of pandemic and vaccine misinformation was politically driven ( 6 ) warrants better communication campaigns and public health strategies which must address vaccine hesitancy and national and global action plans during health crises ( 42 ). This need maybe even more pronounced in countries such as Romania, where the level of Covid vaccination was significantly lower than the level reached in Western European countries ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1980, 56 disasters have occurred in Saudi Arabia, resulting in approximately 4,700 fatalities, 34,000 injuries, and damages amounting to USD 1.87 billion. These events have highlighted the significant challenges faced by Saudi hospitals in disaster management and underscore the necessity for healthcare professionals, particularly nurses, to be wellprepared to mitigate adverse effects on healthcare outcomes (Khatri et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fundamental inclusion of disaster preparation in nursing education, there is a significant gap in the practical knowledge and exposure of nurses to emergency response scenarios. Studies have shown that many nurses lack the required proficiency and confidence in handling emergency situations effectively (Khatri et al, 2023).…”
Section: Introductionmentioning
confidence: 99%